Surgical Reconstruction after Resection of a Large Myxofibrosarcoma of the Upper Extremity - Batista, Kátia Tôrres; Martins, Valney Claudino Sampaio; Schwartzman, Ulises Prieto y; Ferreira, Telma Leonel (Revista Brasileira de Ortopedia, 2019)
Myxofibrosarcoma is a rare soft tissue sarcoma. The authors present a case report regarding the excision and reconstruction of an extensive low-grade myxofibrosarcoma in the forearm, in the wrist, and in the hand of a young woman. A large-scale monobloc excision was performed according to resonance magnetic imaging (MRI) and transoperative histopathologic study findings. A dermal matrix and total skin graft associated with a postoperative physiotherapy program were used. The aspects related to the differential diagnosis of myxofibrosarcoma in a young patient, its infiltrative character, the extensive excision, the reconstruction in two surgical times (using a dermal matrix and a full-thickness skin graft), and the postoperative physical therapy program were considered important.
Keywords: sarcoma; soft tissue neoplasms; rehabilitation